A pricing-based evolutionary cooperative game for sustainable development: a case study on land purchasing. (7th July 2010) - Shen, Huizhang; Yao, Ruipu; Zhao, Jidi; Qiu, Robin G., Zhangjie Ma
Evolutionary Game Theory (EGT) originated from the understanding that frequency dependent fitness introduces a strategic aspect of evolution. In this paper, we apply EGT and dynamics to a sustainable development problem in economic mutualism condition and develop respective evolutionary cooperative games. In particular, we study a land purchase bargaining case in China. Using a fairness line-based dealing model, the bargaining process between the mutualistic players is analysed. Furthermore, by introducing evolutionary cooperative game model, we study the dynamical properties of the game for sustainable development and achieve stable solutions instead of periodical oscillations in traditional EGT such as prey-predator model. Evolutionary stable strategy leads to reciprocal outcomes, i.e. the win-win Nash equilibrium. Simulation results show that evolutionary stable strategies for evolutionary cooperative games depend upon certain specific values of the parameters that construct the strategy space in the evolutionary cooperative games.